2022
DOI: 10.1159/000527151
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance in Prostate Cancer: Current and Potentially Emerging Biomarkers for Patient Selection Criteria

Abstract: <b><i>Background:</i></b> Prostate cancer (PCa) represents one of the most frequent malignancies and the fifth leading cause of cancer death in adult men worldwide. PCa mortality rates have been declining in several Western countries; one of the possible reasons may be related to the application of prostate-specific antigen early detection policies. These early detection protocols increase PCa-specific patient survival; however, a high percentage of these cases corresponds to low-risk P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Therefore, we can probably expect that the present difference between the two groups would be minimised in the modern AS series where patients have a routine upfront MRI scan followed by systematic and targeted biopsies, and where only low-volume GG 2 IRPC patients are included for AS [ 48 , 49 ]. In addition, use of novel biomarkers and molecular genetics [ 50 , 51 ] in assessing disease aggressiveness and selecting appropriate IRPC candidates for AS would further contribute to better oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can probably expect that the present difference between the two groups would be minimised in the modern AS series where patients have a routine upfront MRI scan followed by systematic and targeted biopsies, and where only low-volume GG 2 IRPC patients are included for AS [ 48 , 49 ]. In addition, use of novel biomarkers and molecular genetics [ 50 , 51 ] in assessing disease aggressiveness and selecting appropriate IRPC candidates for AS would further contribute to better oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of PC improves overall patient survival in low-risk patients, but has no effect on the survival of patients with metastatic cancer [ 149 , 150 , 165 ]. Since the management strategy for low-risk patients is active monitoring, careful patient selection and accuracy in risk assessment require new, more precise and more specific biomarkers, since randomized controlled trials have shown that PSA screening has no effect on overall mortality or prostate cancer-caused mortality [ 166 ].…”
Section: Methods For Diagnosing Prostate Cancermentioning
confidence: 99%
“…In the majority of patients, localized PC is multifocal, due to the fact that cancer most often occurs in the peripheral zone of the prostate, the surrounding pseudocapsule is involved in 80% of clinically detected cases of cancer [ 150 , 151 ]. In the following stages, the cancer cells invade the seminal vesicles and paraprostatic tissue, regarded by the international TNM classification as T3, or the urinary bladder, levator muscles, external sphincter and/or anterior abdominal wall, which is the T4 stage [ 151 ].…”
Section: Pathogenesis and Stagingmentioning
confidence: 99%
“…For localized low-and favorable intermediate-risk PC, currently, the best treatment options are radical prostatectomy, radiation therapy or AS. Biomarkers to define the best candidates for these treatments in AS are not addressed in the current review because they were reviewed in a previous work [19]. For unfavorable intermediate-and high-risk PC, current treatments include RP plus extended lymphadenec-tomy, radiotherapy plus ADT and possibly abiraterone for high-risk patients [76,82,84].…”
Section: Current Prostate Cancer Treatments and Potential New Therape...mentioning
confidence: 99%
“…Different types of biomarkers have been studied in PC as tools for the analysis of the risk of progression, with the potential for application in the accurate identification of candidates for active surveillance (AS), adjuvant therapy and/or new therapy modalities. We recently published a review of the role of biomarkers in AS [19]. This review included urine, blood and tissue biomarkers.…”
Section: Introductionmentioning
confidence: 99%